Multidrug-Resistant and Clinically Relevant Gram-Negative Bacteria Are Present in German Surface Waters - Falgenhauer, Linda; Schwengers, Oliver; Schmiedel, Judith; Baars, Christian; Lambrecht, Oda; Heß, Stefanie; Berendonk, Thomas U.; Falgenhauer, Jane; Chakraborty, Trinad; Imirzalioglu, Can (Frontiers in Microbiology, 2019)
Water is considered to play a role in the dissemination of antibiotic-resistant Gram-negative bacteria including those encoding Extended-spectrum beta-lactamases (ESBL) and carbapenemases. To investigate the role of water for their spread in more detail, we characterized ESBL/Carbapenemase-producing bacteria from surface water and sediment samples using phenotypic and genotypic approaches. ESBL/Carbapenemase-producing isolates were obtained from water/sediment samples. Species and antibiotic resistance were determined. A subset of these isolates (n = 33) was whole-genome-sequenced and analyzed for the presence of antibiotic resistance genes and virulence determinants. Their relatedness to isolates associated with human infections was investigated using multilocus sequence type and cgMLST-based analysis. Eighty-nine percent of the isolates comprised of clinically relevant species. Fifty-eight percent exhibited a multidrug-resistance phenotype. Two isolates harbored the mobile colistin resistance gene mcr-1. One carbapenemase-producing isolate identified as Enterobacter kobei harbored blaVIM–1. Two Escherichia coli isolates had sequence types (ST) associated with human infections (ST131 and ST1485) and a Klebsiella pneumoniae isolate was classified as hypervirulent. A multidrug-resistant (MDR) Pseudomonas aeruginosa isolate encoding known virulence genes associated with severe lung infections in cystic fibrosis patients was also detected. The presence of MDR and clinically relevant isolates in recreational and surface water underlines the role of aquatic environments as both reservoirs and hot spots for MDR bacteria. Future assessment of water quality should include the examination of the multidrug resistance of clinically relevant bacterial species and thus provide an important link regarding the spread of MDR bacteria in a One Health context.